Expression of deiodinase 2 (DIO2) and integrin alpha 9 (ITGA9) genes as indicators' of adaptability and their relationship with physio-biochemical parameters in Tharparkar and Karan Fries heifers during different seasons - NAIDU, VELAGALA C SEKHAR; SINGH, S V (The Indian Journal of Animal Sciences, 2018)
The aim of the study was to observe the influence of ambient conditions (seasons) on expression pattern of deiodinase 2 (DIO2) and integrin alpha 9 (ITGA9) genes in peripheral blood mononuclear cells (PBMC) and their relationship with physiological and biochemical parameters of Tharparkar and Karan Fries heifers. Healthy heifers of Tharparkar and Karan Fries breed (6 each) were selected and blood samples were collected from these animals at weekly interval. These blood samples were centrifuged to separate the plasma (for biochemical parameters) and buffy coat (for total RNA isolation). The expression of DIO2 gene was down-regulated during hot humid season and up-regulated during winter season in both the breeds. The DIO2 gene showed a positive correlation with thyroid hormones (T3, T4) and negative correlation with physiological responses (RR, PR, RT, ST), cortisol hormone, antioxidant enzymes (SOD, GPx) and non-esterified fatty-acids (NEFA). The expression pattern of ITGA9 gene was opposite to DIO2 gene, i.e. up-regulated during hot humid season and down-regulated during winter season in both the breeds. ITGA9 gene expression showed a positive correlation with cortisol, antioxidant enzymes, NEFA and physiological responses, and negative correlation with thyroid hormones. The fold change in expression of DIO2 and ITGA9 genes was higher in Karan Fries than Tharparkar heifers during hot humid and winter season. The dry matter intake was lower during hot-humid season than autumn and winter season in both the breeds of heifer. The expression pattern of the DIO2 and ITGA9 genes and their relationship with physio-biochemical parameters revealed the essential role in adaptability of cattle as candidate gene. Based on the results of present study, it can be stated that Tharparkar heifers are better adapted to tropical climatic conditions than Karan Fries heifers.